Flash Fiction Production as Narrative Compression: Transformation of Receipt Parinaaz di Kafe Kroasia in Digital Humanities - Rahmania, Reva Mawarta; Roz, Vanessa Amanda; Fadlia, Mifta Alfinati; Marsa, Armilda Daffa Evelyna (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines the production of flash fiction as a form of narrative compression in transforming the short story Receipt Parinaaz di Kafe Kroasia within the framework of Digital Humanities. The study aims to transform the short story into a 300–500 word flash fiction text through the condensation of narrative structure without eliminating its meaning. In this study, narrative compression is understood as a process of selection, reduction, and reconstruction that produces intensified meaning. This research employs a qualitative approach with narrative analysis focusing on the concept of hypertextuality by Gérard Genette and narrative theory of Marie-Laure Ryan. The analytical stages include identifying the intrinsic elements of the short story, selecting which narrative elements are retained or omitted, and reconstructing the text into a flash fiction as a form of hypertext. The findings show that the production of flash fiction preserve conflicts and the psychological characterization of the protagonist while transforming the narrative into a shorter yet denser structure. The application of narrative compression results in stronger implicit meaning and enhanced emotional resonance. The transformation is presented in the form of a flash fiction script and a digital visualization in the form of a flyer, representing a form of digital literary production within Digital Humanities.